Music and Motivation - Podkrajšek, Maruša (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter examines the role of music in fostering motivation, particularly within the context of education. It explores how music supports the development of intrinsic motivation, self-efficacy, and self-confidence, while enhancing students' academic and social skills. Various teaching approaches are analyzed, including adapting methods, offering students autonomy in choosing activities, and incorporating popular music to boost engagement. The chapter also highlights the importance of creativity and collaboration in cultivating students' long-term connection to music. Practical recommendations for teachers are provided, emphasizing the use of modern technologies and the creation of a stimulating learning environment that enhances musical motivation and nurtures a lasting love of music in students. The chapter combines theoretical insights with practical strategies to improve music education.